The quality of life analysis of knee prosthesis with complete microprocessor control in trans-femoral amputees - Sağlam, Yavuz; Gülenç, Barış; Birişik, Fevzi; Ersen, Ali; Yılmaz Yalçınkaya, Ebru; Yaıcıoğlu, Önder (Turkish Association of Orthopaedics and Traumatology, 2017)
Objective The aim of this study was to analyze the patient demographics, etiology of limb loss as well as reporting SF-36 scores for microprocessor prosthesis users in Turkish population. Methods We reviewed 72 patients (61 male and 11 female; mean age: 37.7 ± 10.7) with uni-lateral, above knee amputation and a history of regular and microprocessor prosthesis use. All patients were called back for a last follow-up and they were asked to fill a self-administered general health status questionnaire (SF-36). Results According to the SF-36 results; physical component score (PCS) score was 46 ± 7.3 and mental components summary (MCS) score was 46.5 ± 9.1. These scores have statistical similarity with Turkish healthy controls, except SF (social functioning) sub-dimension. PCS score for women microprocessor users were significantly lower than men (43.3 vs. 48.7, p = 0.03), but MCS scores were similar in between genders (46 vs. 48.2, p = 0.13). Conventional prostheses usage time was positively correlated with physical function (PF) scores (r = 0.322, p = 0.010). Microprocessor prosthesis usage time was negatively correlated with role limitations due to emotional problem (RE) scores (r = -0,313, p = 0.009). Conclusion The quality of life surveys were showed that the loss of an extremity have higher physical and psychological impact on women's physical scores. Overall, SF-36 results were similar in microprocessor using amputee's and Turkish normal controls. Level of evidence Level IV, therapeutic study.
Keywords: Microprocessor Controlled Prosthesis; Physical Component Summary Score; Quality of Life Analysis; Trans-Femoral Amputees